AN ESR STUDY OF THE DIAMAGNETICALLY DOPED S = 1/2 SQUARE HEISENBERG ANTIFERROMAGNETS CU1-XMGX(HCO2)2.4H2O AND CU1-XZNX(HCO2)2.4H2O - Clarke, S; Harrison, A (1992)
The two-dimensional (2D) S-1/2 Heisenberg antiferromagnet copper (II) formate tetrahydrate (Cu(HCO2)2.4H2O) has been doped with the diamagnetic ions Mg2+ and Zn2+ up to levels of 15 at.%. The temperature dependence of the electron spin resonance (ESR) signal provides a way of accurately determining the differences in the Neel temperatures, TN(x), of samples with different dopant concentrations, x. There is a linear decrease of TN with increasing dopant concentration: TN(x)=(1- alpha x)TN(0) where the constant alpha is 3.4+or-0.1 and TN(0) is the Neel temperature of the undoped material. This behaviour is compared with that of La2CuO4 and other 2D systems. The width of the ESR signal at a particular temperature is also found to decrease with increasing dopant concentration. These features, together with the variation of linewidth with temperature characteristic of 2D systems, are discussed in the light of the interactions between the magnetic ions.